Anterior inferior cerebellar artery aneurysms: Segments and results of surgical and endovascular managements. Issue 6 (December 2016) - Lv, Xianli; Ge, Huijian; He, Hongwei; Jiang, Chuhan; Li, Youxiang
Background: Anterior inferior cerebellar artery (AICA) aneurysms are rare and published clinical experience with these aneurysms is limited. Objective: The objective of this article is to report angiographic characteristics and results associated with premeatal, meatal and postmeatal segments, surgical and endovascular therapies. Methods: A literature review was performed through PubMed using "anterior inferior cerebellar artery aneurysm" through January 2016. Clinical data, angiograms, management techniques, and patient outcomes were reviewed for 47 collected cases in 30 previous reports. Results: Of these aneurysms, 21 (44.7%) were associated with meatal segment, 10 (21.3%) were postmeatal and 16 (34.0%) were premeatal. Patients with meatal aneurysms are more likely to present with subarachnoid hemorrhage and hearing loss and facial palsy (77.8%). Patient outcomes of meatal aneurysms presented with more neuropathies (51.7%) and cerebellar symptoms (14.3%) ( p  = 0.049). Four cases of meatal aneurysm with preoperative cranial nerve deficits (two VII and two VIII) showed improvement after surgery. Endovascular treatment achieved outcomes similar to surgical treatment ( p = 0.327). Conclusions: AICA aneurysms have a predilection for meatal segment. Patients with meatal aneurysms are more likely to present with subarachnoid hemorrhage and hearing loss and facial palsy. Patient outcomes of meatal aneurysms presented with more neuropathies and cerebellar symptoms. Endovascular treatment achieved outcomes similar to surgical treatment.